Photosynthetic characteristics of lichens of genus Umbilicaria from SW Greenland (Nuuk area) in reponse to thallus dehydration. - Barták Miloš; Hansen Eric; Hazdrová Jana; Skácelová Kateřina; Trnková Kateřina; Prošek Pavel (Jagellonian University, 2013)
Thalli of foliose epilithic lichens Umbilicaria arctica and U.hyperborea were collected on the rocks at several locations in the neighbourhood of Nuuk, and transported to the Czech Republic where kept in dry state in dark at 5 oC before experiments. After 48 h rehydration, simultaneous measurements of (1)effective quantum yield (YieldPSII) of photosystem II, (2)photochemical reflectance index (PRI), (3)normalized difference vegetation index (NDVI), (4)chlorophyll fluorescence fast kinetics (OJIP) were made in response to gradual thallus dehydration expressed as water potential (WP). Dehydration-response curves of YieldPSII showed S-curve relationship. In both species, the first signs of inhibition of photosynthetic processes appeared at WP of about -10 MPa. Further dehydration led to a decrease in YieldPSII and, finally, full inhibition of PSII photochemical photosynthetic processes. Critical point for PSII processes was found at WP of about -25 MPa, similarly to other epilithic lichens investigated by this method Vyl studován vztah mezi fůznými fotosyntetickými charakteristikami lišejníků Umbilicaria arctica a Umbilicaria Hyperboera ve vztahu k vyschnutí stélky. Thalli of foliose epilithic lichens Umbilicaria arctica and U.hyperborea were collected on the rocks at several locations in the neighbourhood of Nuuk, and transported to the Czech Republic where kept in dry state in dark at 5 oC before experiments. After 48 h rehydration, simultaneous measurements of (1)effective quantum yield (YieldPSII) of photosystem II, (2)photochemical reflectance index (PRI), (3)normalized difference vegetation index (NDVI), (4)chlorophyll fluorescence fast kinetics (OJIP) were made in response to gradual thallus dehydration expressed as water potential (WP). Dehydration-response curves of YieldPSII showed S-curve relationship. In both species, the first signs of inhibition of photosynthetic processes appeared at WP of about -10 MPa. Further dehydration led to a decrease in YieldPSII and, finally, full inhibition of PSII ...